2020
DOI: 10.1109/tcyb.2019.2891536
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Synchronization of Heterogeneous Networks With a Generalized Markovian Topology and Event-Triggered Communication

Abstract: We consider the quasi-synchronization problem of a continuous time generalized Markovian switching heterogeneous network with time-varying connectivity, using pinned nodes that are event-triggered to reduce the frequency of controller updates and inter-node communications. We propose a pinning strategy algorithm to determine how many and which nodes should be pinned in the network. Based on the assumption that a network has limited control efficiency, we derive a criterion for stability, which relates pinning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…In [28], by developing an event-triggered pinning control mechanism, Wu et al studied the issue of consensus for nonlinear multiagent systems. The quasi-synchronization of networked systems with limited control efficiency was investigated in [29] by using an event-triggered control algorithm. In [30], sufficient conditions for fuzzy CNSs related to the event-triggered communication method and nonuniform sampling interval were derived.…”
Section: Introductionmentioning
confidence: 99%
“…In [28], by developing an event-triggered pinning control mechanism, Wu et al studied the issue of consensus for nonlinear multiagent systems. The quasi-synchronization of networked systems with limited control efficiency was investigated in [29] by using an event-triggered control algorithm. In [30], sufficient conditions for fuzzy CNSs related to the event-triggered communication method and nonuniform sampling interval were derived.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, a number of researchers have suggested that the event-based control algorithms can reduce communication and computation loads in networked systems while maintaining control performance [13][14][15][16][17][18][19][20][21]. Dimarogonas et al [13] investigated centralized and distributed formulation of eventdriven strategies for consensus of multi-agent systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [16,17], consensus problem of second-order multi-agent systems with event-triggered control was investigated. Eventtriggered control was also applied to pinning synchronization problem of complex networks [18][19][20][21]. Lu et al [18] studied pinning synchronization of linearly coupled dynamical systems with time-varying coupling matrix and pinned node set induced by a Markov chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other one is eventdriven mechanism and named as operation mode driven by a Markov chain. During the past decades, a lot of topics on all kinds of MJSs have been studied such as stability [3]- [6], stabilization [7]- [13], H ∞ control [14]- [16] and filtering [17]- [21], fault detection [22]- [24], estimation [25], [26], adaptive control [27], [28], synchronization [29], and so on.…”
Section: Introductionmentioning
confidence: 99%